Effect of alerce (Fitzroya cupressoides) cell culture extract on wound healing repair in a human keratinocyte cell line. (5th September 2019) - Carvajal, Felipe; Duran, Catherine; Aquea, Felipe
Abstract: Background: Fitzroya cupressoides, commonly known as alerce, is an endemic conifer unique to southern South America. Alerce wood is renowned for its durability and resistance to biological degradation due to the presence of a particular class of secondary metabolite. Alerce extracts have been used in traditional medicine for different skin lesion treatments. Aims: To develop a cell culture system to produce alerce extract and evaluate its cytotoxicity and effects on in vitro wound healing. Methods: Cell cultures and aqueous extracts were prepared from alerce needles. Cytotoxicity was evaluated in keratinocytes (HaCaT line) and melanocites (C32 line) using the XTT assay. Wound healing was assayed with the scratch test in HaCaT cells, using mitomycin C to evaluate the role of cell division in the wound closure. Results: Alerce cell culture extract has a significant effect on wound healing at different concentrations. No positive effects on the viability of normal and cancerous skin cells were observed. These results suggest that alerce extracts stimulate cell division in human skin epidermal cells in the context of wound repair. Conclusions: Bioactive compounds extracted from alerce cell cultures show promise as ingredients in dermocosmetic formulations, but further clinical studies are required to support these findings at the tissue level.